Cinnamomum verum J. Presl. Bark essential oil: in vitro investigation of anti-cholinesterase, anti-BACE1, and neuroprotective activity - Mina Saeedi; Aida Iraji; Yasaman Vahedi-Mazdabadi; Atiyeh Alizadeh; Najmeh Edraki; Omidreza Firuzi; Mahdieh Eftekhari; Tahmineh Akbarzadeh (BMC, 2022)
Abstract Background Cinnamomum verum J. Presl. (Lauraceae), Myrtus communis L. (Myrtaceae), Ruta graveolens L. (Rutaaceae), Anethum graveolens L. (Apiaceae), Myristica fragrans Houtt. (Myristicaceae), and Crocus sativus L. (Iridaceae) have been recommended for improvement of memory via inhalation, in Iranian Traditional Medicine (ITM). In this respect, the essential oils (EOs) from those plants were obtained and evaluated for cholinesterase (ChE) inhibitory activity as ChE inhibitors are the available drugs in the treatment of Alzheimer's disease (AD). Methods EOs obtained from the plants under investigation, were evaluated for their potential to inhibit acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) in vitro based on the modified Ellman's method. The most potent EO was candidate for the investigation of its beta-secretase 1 (BACE1) inhibitory activity and neuroprotectivity. Results Among all EOs, C. verum demonstrated the most potent activity toward AChE and BChE with IC50 values of 453.7 and 184.7 µg/mL, respectively. It also showed 62.64% and 41.79% inhibition against BACE1 at the concentration of 500 and 100 mg/mL, respectively. However, it depicted no neuroprotective potential against β-amyloid (Aβ)-induced neurotoxicity in PC12 cells. Also, identification of chemical composition of C. verum EO was achieved via gas chromatography-mass spectrometry (GC-MS) analysis and the major constituent; (E)-cinnamaldehyde, was detected as 68.23%. Conclusion Potent BChE inhibitory activity of C. verum EO can be considered in the development of cinnamon based dietary supplements for the management of patients with advanced AD.